Penguatan Kompetensi Mahasiswa Melalui Program Pendampingan Sahabat Daya: Model Pembelajaran Experiental Learning Pemberdayaan Ibu Prasejahtera Produktif - Heidy Paramitha Devi; Dea Nanda Putri Natsaya; Moh. Ubaidillah (Universitas PGRI Madiun, 2026)
Productive underprivileged mothers as ultra-micro entrepreneurs in Ponorogo Regency play a crucial role in supporting their families' finances. However, they still face various challenges, such as poor financial management skills, the lack of separation between business and household finances, dependence on daily capital, low digital media utilization, the lack of informative business profiles, and low awareness of business legality. This community service activity aims to increase business capacity through the BTPN Syariah Sahabat Daya Program using a participatory mentoring approach. The program was implemented from August to December 2024 at one BTPN Syariah center in Ponorogo Regency, involving 10 productive underprivileged mothers, one student as a facilitator, and one lecturer as a mentor. Mentoring is carried out through needs identification, education, practice, monitoring, and evaluation with a minimum frequency of four visits per partner. The results of the activity showed an increase in partner capacity: 80% were able to maintain simple financial records, 70% began separating business and household finances, 60% began managing business capital more systematically, 90% were proficient in utilizing digital media for promotion, 70% had informative business profiles, and 40% were willing to apply for a Business Identification Number (NIB). This program also strengthened students' competencies in community mentoring and served as a model for university-industry collaboration that supports the sustainable empowerment of ultra-micro businesses